Multifrequency low-level laser-assisted mastopexy in 231 consecutive patients: a dataset (2025)
Breast ptosis, the inferior displacement of the nipple–areola complex, is predominantly attributed to age-related collagen degradation within the breast parenchyma as a result of fibroblast senescence and postmenopausal estrogen depletion, which together result in skin ageing and mammary adipose tissue reduction. This Dataset reports the clinical information and measurements of 231 patients who underwent multifrequency low-level laser-assisted mastopexy. Data were collected prospectively between February 2021 and November 2023. All patients' references and identification data were anonymized to ensure compliance with Colombian legal regulations. Subsequently, data were translated from Spanish to English and stored in both.xls and.csv formats. This study aimed to evaluate the effect of the procedure on breast ptosis degree and the sternal notch to nipple distance (SNND) to assess the evolution of breast ptosis. This article presents demographic, personal, and familial history data, anthropometric measurements, breast ptosis degree classified according to the Regnault system, SNND measurements, and complications categorized using the Clavien-Dindo classification system.